GUIDANCE IN UTILIZING TIKTOK AS A DIGITAL MARKETING MEDIA TO INCREASE THE MARKET REACH OF SOTO PAK ZAINAL'S MSMES - Ilyasa Ramadhanov Annaafi; Ridwan Habibi; Mahendra Aprilino; Agus Dwi Cahya (EMPOWERING HUMANITY, 2026)
Mentoring activities were carried out at the Soto Pak Zainal MSME as an effort to assist business actors in developing marketing and expanding market reach through the use of digital media. Mentoring was carried out through field observations and direct interviews with business owners to understand business conditions, implemented marketing patterns, and obstacles faced in using social media. Based on the results of these observations and interviews, students provided suggestions and recommendations for digital marketing strategies by utilizing TikTok social media as a promotional tool. The use of TikTok focused on presenting product visuals, the manufacturing process, and engaging and consistent content. Through this mentoring activity, it is hoped that Soto Pak Zainal MSME can increase market reach and have a better understanding of how to utilize social media as an effective and sustainable marketing tool.